Development Of Virtual Reality Gis For Cultural Heritage Conservation (Case Study: Sewu Temple) - Threesiana, Ririn; Suwardhi, Deni; Riyanto, Sugeng (Indonesian Journal of Geospatial, 2013)
Abstract. Cultural heritage is an asset owned by any country that can tell behavior of peopleâs life there. The story of the cultural heritage â one of them contained in archaeological object â is a story that have historical value and can not be replaced so we need to make the right efforts to conserve them, such as documenting the archaeological object we have, in this case is Sewu Temple Complex in Klaten, Central of Java. Conservation mean as branch of archeology that tries to preserve and manage archeological object to a lot of academic-practical interest (Yuwono, 2003). Geographic Information System that have storing, showing, and analyzing data ability, in the scope of conservation can used by archeologist for conserve or reconstruction. Principle of the development of virtual reality GIS for cultural heritage conservation is more directed to the terms of visualization. The several stage of this study are design the spatial database, data extraction â includes 3D modeling, 3D model georeferencing, 3D model segmentation, database implementation, and visualization process. The expectation result for this virtual reality GIS is an application that will represent 3-D visualization of Sewu Temple area, 3D models of each part of temple at LOD 2, LOD 3, until LOD 4. Beside that the application can be used for Temple reconstruction for more efficiently and effectively process.Â Keywords : Database, Virtual Reality GIS, Conservation, 3D ModelsÂ